posted by Anonymous on .
For a function f, let f*(x) = lim as h→0 be [f(x+h) - f(x-h)]/h
a) Determine f*(x) for f(x) = cosx
b) write an equation that expresses the relationship between the functions f* and f` where f` denotes the usual derivative of f
Use the trigonometric identity
cos (x + h) = cosx cosh - sinx sinh
This means that
cos(x + h) - cosx
= (cosh -1) cosx - sin x sinh
For very small h, sin h = h and cos h = 1, so [cos(x + h) - cosx]/h -> -sin x
-sin x is the exact derivative of cos x.